Faszyzm włoski wobec kwestii żydowskiej 1919–1938 - Podemski, Piotr (Wydawnictwo Uniwersytetu Wrocławskiego, 2012)
The purpose of the paper is to present an issue, little-known in Poland, of an approach of Italian Fascism to the Jewish question until the time of the publication of the racist manifesto 1938. The article analyzes the evolution of the Fascist regime’s policies towards Jews during the 1919–1937 period, attempting to explain the origin of the decision to start their discrimination and persecution. In liberal Italy the phenomenon of anti-Semitism did not exist, except for some Catholic circles. Seizing political power in 1922, Mussolini’s regime did not reveal any intentions to change this state of affairs. From the very beginning, both Jews and anti-Semites for instance, Preziosi, Orano or Interlandi were represented in the Fascist ranks. Up until 1934 mutual relations remained very positive, which was symbolized by Fascist Italy’s ambitions to extend its patronage to the Zionist movement in order to facilitate its own colonial conquests. There is acontinuing scholarly debate over the reasons for the change of this policy during the 1934–1937 period. Among probable causes for such an occurrence different authors enumerate, for example, an ultimate inevitability of the adoption of racist policies in atotalitarian nation-state, the influence of the Nazi Germany, transference to Jews of racism previously practiced in African colonies, the accusations leveled against them of harming Italy on the international scene and of exhibiting seditious and communist tendencies allegedly expressed, for example, in inciting the Spanish civil war. The author is inclined to support the theory of the “antisemitization” of colonial racism, although he also admits that the described turn of events would not have been possible without the concurrent emergence of at least afew other factors mentioned before. The author intends to devote aseparate article to the analysis of Jews’ situation during the time of Italian persecution 1938–1943 and to their subsequent extermination during the German occupation.
Keywords: Italian Fascism; Jews; anti-Semitism